An Ethnopedagogical Approach in Developing Inferential Reading Materials in EFL Contexts: Integrating Lampung Local Wisdom - Septiyana, Linda; Suprihatin, Yeni; Ninsiana, Widhiya (Jurnal Pedagogy, 2025)
Ethnopedagogy emphasizes the integration of local wisdom into educational practices and has gained increasing attention in EFL contexts. This study aimed to develop inferential reading materials by integrating Lampung local wisdom through an ethnopedagogical approach. Employing a research and development (R&D) design based on the Thiagarajan and Semmel 4D model, the study involved four stages: define, design, develop, and disseminate. During the define stage, students’ needs were examined through questionnaires and interviews. The design stage focused on syllabus development and the selection of reading theories, strategies, text genres, and culturally relevant materials rooted in Lampung local wisdom. In the develop stage, an inferential reading textbook was produced and validated by experts, while the disseminate stage examined students’ responses to the materials. The participants consisted of one inferential reading lecturer and 70 undergraduate students from an English Education program at a public higher education institution in Indonesia. The findings reveal a strong need for culturally grounded inferential reading materials, as existing resources insufficiently support students’ inferential comprehension skills. Students’ responses indicated a highly positive evaluation of the materials in terms of relevance, clarity, and cultural integration, with a mean score of 3.48 on a 4-point scale, categorized as very good. These results suggest that an ethnopedagogical approach is both effective and feasible for developing inferential reading materials in EFL higher education contexts.